"It's hard to find balance when you're broken": Exploring female endurance athletes' psychological experience of recovery from relative energy deficiency in sport (RED-S). Issue 1 (February 2022) - Langbein, Rachel K.; Martin, Daniel; Allen-Collinson, Jacquelyn; Jackman, Patricia C.
Highlights: RED-S recovery was characterised by significant psychological conflict Psychological conflict was triggered by personal, social, and sport-specific factors Maladaptive cognitions and emotions encouraged the adoption of LEA behaviours Adaptive cognitions and emotions facilitated optimal EA and physical recovery Varying degrees of eating psychopathology were associated with RED-S recovery Abstract: Introduction: This study aimed to explore qualitatively the psychological experience of recovery from relative energy deficiency in sport (RED-S). More specifically, it sought to understand: how RED-S is experienced from a psychological perspective; sources of psychological conflict in the ongoing management of energy availability (EA); and athlete responses to psychological conflict in the pursuit of optimal EA. Methods: Eight female endurance athletes identifying as "in recovery" or "recovered" from RED-S ( M age = 29.78 years) participated in this integrated methods multiple case-study. Participants engaged in an initial topical life history interview, before completing an online diary over a 21-day period, taking photographs of psychological triggers for seven days, and participating in a follow-up interview. Data were analysed using reflexive thematic analysis. Results: The theme in too deep and treading water captured the significant psychological implications of RED-S. Seven sources of psychological conflict reported while managing EA were identified. The theme a constant tug of war represented the responses to these sources of psychological conflict in the ongoing management of EA. Within this theme, the subthemes in two minds and an emotional rollercoaster illustrated the cognitive and affective responses to psychological conflict, while giving in and the only way is through represented the adaptive and maladaptive behavioural responses during recovery, respectively. Conclusion: This study offers novel insights into the complex nature of recovery from RED-S and highlights the importance of considering psychological factors underpinning improved physiological functioning and overall wellbeing during RED-S recovery.